ROLE OF COOPERATIVE LEARNING IN ENHANCING STUDENTS’ WRITING SKILLS IN PAKISTANI COLLEGES: A REVIEW OF LITERATURE - Muhammad Siddique; Manvender Kaur Sarjit Singh (Proceedings of The ICECRS, 2016)
The current study examined the causes of poor writing skills of intermediate students in the public sector colleges of Pakistan. Besides, the study discusses the methods being used in these colleges and how those methods can be replaced by cooperative and collaborative learning techniques to enhance the writing skills of the students successfully and effectively. Research conducted so far in Pakistani context indicated that a large number of students in Pakistan fail due mainly to their poor writing skills as writing is being instructed through rote learning in teacher-centered classroom. To tackle this issue of students’ poor writing skills, the paradigm needs to be shifted from rote learning to cooperative learning. The paper purports to explore as to why pedagogues in Pakistan are employing rote learning and teacher centered approach for the instruction of writing skills. To explore this issue, the paper employed the technique of review of literature. The findings indicated that the lecturers employed the conventional methods to teach writing skills especially descriptive essay writing skills. The literature reviewed showed that large classes, maintaining discipline, compulsion to complete the course in time are the causes of lecturers’ sticking to such conventional methods. Besides, the current paper gives recommendations for the enhancement of writing skills which include encouragement of group work, face to face interaction and discussion as learning strategies. Finally, to attain this objective, the current study recommends the employment of cooperative and collaborative learning strategies for the improvement of intermediate students’ descriptive essay writing skills.